GREEN HUMAN RESOURCES MANAGEMENT AND SUSTAINABLE ORGANIZATIONAL PERFORMANCE: THE MEDIATING ROLE OF EMPLOYEE ECO-INNOVATION - Karyono Karyono; Giri Nur Pribadi; Erina Rulianti (Jurnal Media Ekonomi (JURMEK), 2026)
Purpose: This study examines the influence of Green Human Resource Management (Green HRM) on Sustainable Organizational Performance and investigates the mediating role of Employee Ecological Innovation in this relationship. Methodology: A quantitative explanatory approach with a cross-sectional design was employed. Data were collected from 420 middle-level managers and employees working in manufacturing and service companies across Indonesia, Malaysia, and Thailand. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Results: Findings indicate that Green HRM has a positive and significant effect on Sustainable Organizational Performance (β = 0.214; p < 0.001). Green HRM is also a strong predictor of Employee Ecological Innovation (β = 0.587; p < 0.001). Furthermore, Employee Ecological Innovation significantly influences Sustainable Organizational Performance (β = 0.492; p < 0.001). Most importantly, Employee Ecological Innovation partially mediates the relationship between Green HRM and Sustainable Organizational Performance (β = 0.289; p < 0.001). Conclusion: Green HRM contributes not only directly to sustainable performance but also indirectly by enhancing employees’ ecological innovation capabilities. Green policies that stimulate creativity and environmentally oriented problem-solving among employees are effective in improving economic, environmental, and social outcomes simultaneously. Limitations: The cross-sectional design limits causal inference. Future studies should adopt longitudinal designs and include moderating variables such as transformational leadership or regulatory pressure. Contribution: This study extends Resource-Based View (RBV) and Ability-Motivation-Opportunity (AMO) theory by positioning employee ecological innovation as a valuable, inimitable intangible resource for sustainable organizational performance.